ЭЛЕКТРОМАГНИТНЫЙ ПЕРЕМЕШИВАТЕЛЬ ЖИДКОГО МЕТАЛЛА С ПООЧЕРЕДНЫМ ДЕЙСТВИЕМ БЕГУЩЕГО И ПУЛЬСИРУЮЩЕГО МАГНИТНЫХ ПОЛЕЙ - Глухенький , А.И.; Гориславец , Ю.М.; Максименко , В.Ю. (Інститут електродинаміки НАН України, Київ, 2014)
Electromagnetic system for liquid metal stirring in melting furnaces and mixers which creates alternately travelling and pulsating magnetic fields is presented. For such combined stirrer the 3D computer modelling of electromagnetic and hydrodynamic processes is carried out. The electromagnetic computations were performed at given coils voltages in the system. The hydrodynamic computations were made for both stationary and non-stationary conditions. As shown, the periodic alternation of travelling and pulsating magnetic fields allows realize effective metal stirring in all space of furnace bath. The electromagnetic and hydrodynamic characteristics of the stirrer are obtained. References 3, tables 1, figures 2.